2007
DOI: 10.1080/17453670710013906
|View full text |Cite
|
Sign up to set email alerts
|

Safe fixation with two acetabular screws after Ganz periacetabular osteotomy

Abstract: Background and purpose With Ganz periacetabular osteotomy, the osteotomized acetabular fragment is reoriented in an adducted, extended, and rotated position. The acetabular fragment is fixated with 2 screws and the patients are allowed 30 kg of weight bearing immediately after surgery. We were interested in examining the stability of the reoriented acetabulum after Ganz osteotomy; thus, the migration of the acetabular fragment was assessed by radiostereometry.Patients and methods 32 dysplastic patients (27 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…Comparing the original Tönnis angles (Table 1) with those determined at the optimal CE angle (Table 6), the optimal CE angle position represents a reduction in Tönnis angle for hips CE10, CE13, CE20, and CE29, to angles that were either within or close to what is considered the normal range, 1–10° 10. The Tönnis angle for CE28 was increased slightly at the optimal CE angle; however, this may be due to the abnormal shape of the head for this hip.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the original Tönnis angles (Table 1) with those determined at the optimal CE angle (Table 6), the optimal CE angle position represents a reduction in Tönnis angle for hips CE10, CE13, CE20, and CE29, to angles that were either within or close to what is considered the normal range, 1–10° 10. The Tönnis angle for CE28 was increased slightly at the optimal CE angle; however, this may be due to the abnormal shape of the head for this hip.…”
Section: Resultsmentioning
confidence: 99%
“…The CE angle in a normal hip is >25°. A hip with a CE angle <20° may be diagnosed as DDH 9, 10. The periacetabular osteotomy (PAO) to correct DDH depends on the clinical condition of the patient and the severity of the disease 8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The approach involves minor incision of the soft tissue and early mobilization ( Troelsen et al 2000 ). Radiological follow-up ( Mechlenburg et al 2007 , 2009 ) and clinical follow-up ( Troelsen et al 2000 ) after minimally invasive PAO have been reported, but little is known about objective measures of physical function. Decreased hip flexion moment and reduced walking speed in patients undergoing PAO have been reported in 2 prospective studies ( Pedersen et al 2006 , Sucato et al 2010 ).…”
mentioning
confidence: 99%
“…At this stage, the applicability of an intrapelvic plate was determined; however, because previous biomechanical studies showed that 2 screws were sufficient for ideal fixation, plate fixation was not performed. 21 …”
Section: Methodsmentioning
confidence: 99%